Prevention of Musculoskeletal Injuries Amongs Manufacturing Operators Using REBA and Nordic Body Map to Develop Karakuri-based Tools - Triarti Saraswati (Jurnal Ergonomi dan K3, 2020)
In Indonesia, human labors are the most workers in manufacturing industries, they have low level of education and skills, easy to replace with low wages. Their welfare mostly ignored by management eventhough complaints of pain and body discomfort released to supervisors. This research was conducted in order to analyze body postures among manufacturing workers with purpose to minimize health impact to the workers. Research started with literature studies, data gathering using Nordic musculoskeletal questionnaire and REBA then processed using Excell and then analized to find solution for this problem. This research was conducted in several different manufacturing industies, such as packaging department in shoes manufacturing, automotive, sorting and inspection in paper industry and assembly department in electrical panel industry; since all of these industries still rely on human workers in one or more department(s) within the manufacturing plant. Complaints and discomfort of these workers were measured using Nordic musculoskeletal questionnaire and REBA was used to analize their posture and scored to assess the safety of the postures. Complaint on their back, waist, hand and feet are common in the assembly panel workers while similar complaints also reported by workers in sorting and inspection in the paper industry. REBA findings suggest that workers postures should be immediately improved to minimize harm and prevent injury for workers. But, some posture still poses risk then should be improved using support tools, such as adjustable table to assist worker in doing their task. Ergonomics evaluation also needed to ensure the health risk was minimized with the new way of doing their tasks.